Screening for mismatch repair deficiency in colorectal cancer: data from three academic medical centers. (3rd May 2017) - O'Kane, Grainne M.; Ryan, Éanna; McVeigh, Terri P.; Creavin, Ben; Hyland, John MP.; O'Donoghue, Diarmuid P.; Keegan, Denise; Geraghty, Robert; Flannery, Delia; Nolan, Carmel; Donovan, Emily; Mehigan, Brian J.; et al.
Abstract: Reflex immunohistochemistry (rIHC) for mismatch repair (MMR) protein expression can be used as a screening tool to detect Lynch Syndrome (LS). Increasingly the mismatch repair‐deficient (dMMR) phenotype has therapeutic implications. We investigated the pattern and consequence of testing for dMMR in three Irish Cancer Centres (CCs). CRC databases were analyzed from January 2005–December 2013. CC1 performs IHC upon physician request, CC2 implemented rIHC in November 2008, and CC3 has been performing rIHC since 2004. The number of eligible patients referred to clinical genetic services (CGS), and the number of LS patients per center was determined. 3906 patients were included over a 9‐year period. dMMR CRCs were found in 32/153 (21%) of patients at CC1 and 55/536 (10%) at CC2, accounting for 3% and 5% of the CRC population, respectively. At CC3, 182/1737 patients (10%) had dMMR CRCs ( P < 0.001). Additional testing for the BRAF V600E mutation, was performed in 49 patients at CC3 prior to CGS referral, of which 29 were positive and considered sporadic CRC. Referrals to CGS were made in 66%, 33%, and 30% of eligible patients at CC1, CC2, and CC3, respectively. LS accounted for CRC in eight patients (0.8%) at CC1, eight patients (0.7%) at CC2, and 20 patients (1.2%) at CC3. Cascade testing of patients with dMMR CRC was not completed in 56%. Universal screening increases the detection of dMMR tumors and LS kindreds. Successful implementation of this approach requires adequate resources for appropriate downstream management of these patients. Abstract : Universal screening for MMR deficiency using IHC has been recommended as a screening tool for Lynch Syndrome and is increasingly performed as a molecular predictor of response to immune checkpoint inhibition. Over half of patients in our study with dMMR colorectal cancer did not have downstream investigations for Lynch Syndrome. Successful implementation requires appropriate resourcing to ensure complete cascade testing.